2021
DOI: 10.3168/jds.2020-19181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein level and methionine supplementation on dairy cows during the transition period

Abstract: Cows experience a significant negative protein balance during the first 30 d of lactation. Given the functional effects of AA on health, especially in challenging periods such as calving, higher levels of protein and specific AA in the diet may act to improve health and feed intake. The response of dairy cows to 3 protein supplementation strategies during the transition period and through the first 45 d in milk was evaluated. The final data set had 39 Holstein cows blocked based on parity (primiparous vs. mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Feeding RPM to dairy goats had no effect on milk yield, ECM, fat percentage and protein percentage (Al‐Qaisi & Titi, 2014). One hypothesis is that the increased supply of AA was insufficient to induce a responses (Cardoso et al, 2021). Contrary to that, feeding RPM to lactating goats resulted in higher milk production (Cardoso et al, 2021; Poljičak‐Milas & Marenjak, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding RPM to dairy goats had no effect on milk yield, ECM, fat percentage and protein percentage (Al‐Qaisi & Titi, 2014). One hypothesis is that the increased supply of AA was insufficient to induce a responses (Cardoso et al, 2021). Contrary to that, feeding RPM to lactating goats resulted in higher milk production (Cardoso et al, 2021; Poljičak‐Milas & Marenjak, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that the increased supply of AA was insufficient to induce a responses (Cardoso et al, 2021). Contrary to that, feeding RPM to lactating goats resulted in higher milk production (Cardoso et al, 2021; Poljičak‐Milas & Marenjak, 2007). Increased milk production in the 16% CP diet indicated that response to RPM is dependent on the amount of CP in the diet (Cardoso et al, 2021; Lara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma TG was determined by an automatic biochemical analyzer (CLS880, Jiangsu Zecheng Biotechnology). NEFA, b -hydroxybutyric acid (BHBA), immunoglobulin G, A, and M (IgG, IgA, IgM), interleukin (IL-2, IL-6, IL-8, IL-10), tumor necrosis factor (TNF-a), myeloperoxidase (MPO), and serum amyloid A (SAA) were detected using the ELISA method (fully automated ELISA machine, THERMO Multiskan Ascent) (41,42).…”
Section: Compositionmentioning
confidence: 99%
“…Studies also tried to identify the effects of formulating diets for ruminants focusing on the balance of limiting AA. Researchers observed a 2.0 kg/d of DMI increase in cows fed a 15.6% CP diet prepartum compared with a 13.8% CP diet, and a tendency for increased DMI prepartum (1.6 kg/d) by methionine (Met) supplementation of the higher CP diet ( Cardoso et al, 2021 ). Additionally, cows on the higher CP diets had greater IL-1 concentration in blood postpartum and tended to produce 1.75 kg/d more milk than cows fed the low protein diet during the first 45 d of lactation, regardless of Met supplementation.…”
Section: Feeding Strategies To Improve Immunometabolismmentioning
confidence: 99%